Efisiensi Teknis Produksi Bawang Merah di Desa Campur, Kecamatan Gondang, Kabupaten Nganjuk - Putri, Arifatur Rahma; Roidah, Ida Syamsu; Syah, Mirza Andrian (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Onion crop production has steadily increased year after year, although productivity remains variable. Inefficiency arises from the technically inefficient selection of production input factors. The research was aimed to 1) analyze how it impacts during the application of shallot production input factors, 2) determine the value of the technical efficiency of the application of production factors, and also 3) identify the variables which contribute the occurrence of inefficiencies during the production of shallot commodities. This research method was used the stochastic frontier, program 4.1. The sample number was 70 shallot farmers. Primary data is collected by observations, distributing questionnaires, and literature reviews. The result showed that land area and seeds had a considerable impact on technical efficiency, whereas labor, insecticides, and fertilizers had no significant impact. The total average of farmers was found to be technically efficient, with a score of 0.7328. While the varying age of the farmers had a considerable impact on technical inefficiency. The dummy variable of the farmer's occupation, along with the farmer's most recent education, had a negative impact on technical inefficiency. The number of family members, agricultural experience, and frequency of extension visits showed no significant effect on technical inefficiency.